PENGARUH STRUKTUR KEKAR TERHADAP KESTABILAN LERENG DINDING BAGIAN BARAT DAYA DAN TIMUR LAUT PADA DESAIN FASE 6 TAMBANG TERBUKA BATU HIJAU PT NEWMONT NUSA TENGGARA - Yunita Sustriani (Geological Engineering E-Journal, 2013)
One of the safety factors that are important in mining (open pit mining) is a potential landslide on the slopes of the mine wall. Landslides caused by two factors, namely external and internal factors. External factors such as mining itselfis blasting, excavation, loading and material transport. While internal factors, namely the existence of geologicalstructures or areas of discontinuity in the form of joint, faults, folds, veins, the condition of the rock mass, and slopehydrology. Due to the geological structure is one of the important factors controlling the stability of the slope, then atThe studies will be discussed on the influence of geological structures is mainly joint structure. To determine the influence of joint structure on slope stability conditions used two methods of analysis methods ofkinematic and limit equilibrium analysis methods. In the kinematic analysis software used to analyze data Dips generaldirection joint, shear joint zones, veins, face slopes and friction angle. The second method is the method of limitequilibrium analysis with the help of Slide ver 5.0 software using the data in the form of rock strength and the cohesionand friction angle in the studied slope geometry. From the analysis in that the slope can be part of Southwest wedge avalanches are possible, several nondaylightingfailure avalanches both wedge and fields on the Northeastern slope. From the analysis of equilibriumanalysis on the inner walls Southwest FK impaired, when there is a joint structure FK 1,376 before getting jointstructure FK value 1,417. And on the slopes of the Northeast, FK values before exposure to joint structure is 1,432 andafter exposure dropped to 1,177 joint structure which means the slopes in landslides condition. Joint structures thatdirectly affect the stability of a slope is stocky with criteria and slope direction parallel to the face of the slope, the closerthe distance stout slopes face, the amount of joint, stocky and thick. From the analysis on the Northeast slope, slope in acritical condition that FK <1,2. It needs to be done to minimize the angle of slope face.